The Patterns of Classroom Interaction in an EFL Classroom at ELS-Poso english Course - Asri, Nur Hanifa; Lantu, Ika Paramitha; Patau, Sartika Andi (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research aims to find out the classroom interaction patterns and the dominant interaction patterns used in an EFL classroom at English Language Skill (ELS)-Poso English course. In order to analyze the data, the researchers use a theory from Ur (1996) about the patterns of classroom interaction. This research use qualitative research methods and use observations, interviews and field notes to collect the data. The subjects in this research are a tutor and 8 level two students at English Language Skill (ELS)-Poso English Course. The research results show that there are seven interaction patterns used in the level two class at English Language Skill (ELS)-Poso English Course, namely; group work, closed-ended teacher questioning (IRF/IRE), individual work, choral responses, student initiates-teacher answers, full-class interaction, and open-ended teacher questioning. The dominant interaction patterns used in level two class are group work and choral responses.